SISTEM INFORMASI PEMANFAATAN RUANG KOTA KUNINGAN BERBASIS WebGIS (Studi Kasus : Badan Perencanaan Pembangunan Daerah Kabupaten Kuningan) - Fitra Nugraha; Aji Permana (Cloud Information, 2018)
researcher took the theme "Webgis based Information Systems of Space Utilization in Kuningan Regency (A Case Study at Regional Development Planning Agency Kuningan)". The location of this research is done in Kuningan Regency. This research will be focused on the first problem i.e. how to use space in Kuningan is, second, how to show information about city spatial more quickly and accurately is. The purpose of this study is to facilitate in obtaining information on spatial and non spatial data quickly about the use of space in the district of Kuningan and by using digital map is expected to obtain information more integrated between spatial and non spatial data. This research can be useful among others that can be practically used as a reference by stakeholders in the utilization of space. The results of this study are expected to provide references in the field of academic computer science, especially in the field of information systems. The method used in the process of geographic information system development of space utilization mapping in Kuningan uses waterfall model. The analytical approach uses structured analysis. The programming language used in this research is PHP with MySQL as database, while for the development of GIS-based mapping tools uses ArcGIS or ArcMap and then the .shp file format is converted into .jpeg or .png format. Spatial use in Kuningan District is implemented with existing map based on planning result from local government of Kuningan Subdistrict.Keywords: Information System, Urban Space Utilization, GIS, Webgis, digital map